Effect of biofuel co-products in pig diets on the excretory patterns of N and C and on the subsequent ammonia and methane emissions from pig effluent - G. Jarret; J. Martinez; J.-Y. Dourmad (Animal, 2011)
This study was conducted to investigate the effects of incorporation into pig diets of 20% of different co-products from the biofuel industries, which are rich in fibre, on animal growth performance, on nitrogen (N) and carbon (C) excretions, and on the subsequent ammonia volatilisation and methane production during the storage of slurry. Five experimental diets mainly based on wheat and soyabean meal were formulated: two control diets, a control high-protein (CHP) diet with 17.5% of crude protein (CP) and a control low-protein (CLP) diet with 14.0% of CP and three experimental diets with 20% of (i) dried distiller’s grain with solubles (DDGS), (ii) sugar beet pulp (SBP) or (iii) fatty rapeseed meal (FRM). The animals used (20 castrated males) were housed individually in metabolism cages and fed one of the five diets (i.e. four pigs per diet). Urine and faeces were collected separately from each pig in order to measure nutrient digestibility and the excretory patterns of N and C. For each diet, ammonia volatilisation was measured from samples of slurry subsequently produced, over a 16-day storage period in a laboratory pilot scale system. The ultimate methane potential (B0, expressed in litres CH4/kg organic matter (OM)) was measured from the same slurry, for each diet, in anaerobic storage conditions over 100 days. The addition of sources of fibres to the diet decreased (P < 0.05) the animal growth performance by 13% and increased (P < 0.05) the amount of faeces excreted by 100%, whereas the amount of urine was not affected. For the high-fibre diets, there was a shift of N partitioning from urine to faeces, resulting in a much higher faecal N excretion (10 v. 5 g N/pig per day). Concurrently, the fibre enrichment in diets significantly increased (P < 0.05) the C content of the faeces by 68%. Ammonia emission from slurry was significantly reduced (P < 0.05) by 19% to 33% for the high-fibre diets, compared to the CHP diet. Ammonia emission was also reduced (P < 0.05) by 33% for the CLP compared to the CHP diet. B0 values ranged from 428 to 484 l CH4/kg OM. When these are expressed per pig and per day, the B0 from slurry was, on average, 70 l for the two control diets, and 121, 91 and 130 l for the slurry originating from the DDGS, SBP and FRM diets, respectively.